2017
DOI: 10.7755/fb.115.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of courtship acoustics and geophysical features at spawning sites of black grouper (Mycteroperca bonaci)

Abstract: Abstract-Geomorphological assessments were conducted and passive acoustic recordings were collected from 2012 through 2014 at 3 recently identified spawning aggregations of the black grouper (Mycteroperca bonaci) in Puerto Rico and southern Florida. A time series of courtshipassociated sounds (CASs) by black grouper were analyzed in relation to lunar and diel periodicities, water temperature, and tidal stage. Analysis of CAS recordings indicated similar temporal patterns at the 3 spawning aggregations. Spawnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…For black grouper, peak calling before sunset at Site B and compared to the less prominent peak at Site A could also indicate that Site B is closer to the preferred spawning location for this species. There was a similar peak in calling at a black grouper spawning aggregation in Puerto Rico (Schärer et al 2014) and at Riley's Hump, located in the Tortugas South Ecological Reserve, Florida (Sanchez et al 2017). Without recordings for both sites during the same time period or knowing when peak spawning actually occurs for these species (i.e.…”
Section: Temporal Calling Trendsmentioning
confidence: 87%
“…For black grouper, peak calling before sunset at Site B and compared to the less prominent peak at Site A could also indicate that Site B is closer to the preferred spawning location for this species. There was a similar peak in calling at a black grouper spawning aggregation in Puerto Rico (Schärer et al 2014) and at Riley's Hump, located in the Tortugas South Ecological Reserve, Florida (Sanchez et al 2017). Without recordings for both sites during the same time period or knowing when peak spawning actually occurs for these species (i.e.…”
Section: Temporal Calling Trendsmentioning
confidence: 87%
“…We suspect that WDR could have potential as a spawning aggregation site similar to Riley's Hump, a documented multispecies FSA utilized by both snapper and grouper species at different times of the year, which is located 70 km away from Key West in the Dry Tortugas region and has been protected as a no‐take marine reserve since 2001 (Locascio and Burton ; Sanchez et al. ; Feeley et al. ).…”
Section: Reproductive Information Summary For Grouper Tagged In This mentioning
confidence: 99%
“…This location was identified as a potential FSA site for multiple species of snapper (Lindeman et al 2000) and is well known as an FSA site for Permit (Brownscombe et al 2020). We suspect that WDR could have potential as a spawning aggregation site similar to Riley's Hump, a documented multispecies FSA utilized by both snapper and grouper species at different times of the year, which is located 70 km away from Key West in the Dry Tortugas region and has been protected as a no-take marine reserve since 2001 (Locascio and Burton 2015;Sanchez et al 2017;Feeley et al 2018). If the WDR area is an FSA for multiple species year-round, spatial protection could increase larval production and encourage growth of FSAs during both summer and winter months, similar to Riley's Hump.…”
mentioning
confidence: 97%
“…Monitoring, recording and reporting sponge disease/bleaching outbreaks, subsequent die-offs and/or recovery events of large and morphologically diverse species (and their associates) is crucial to assess the overall health of the ecosystem in an ever-changing environment (Wulff, 2013;Deignan et al, 2018;Pita et al, 2018). For example, at Bajo de Sico seamount, an important Nassau and Black grouper aggregation site in Puerto Rico (Tuohy et al, 2015;Sanchez et al, 2017), occurrence of disease and bleaching was observed affecting several large specimens of X. muta at depths between 35 and 50 m (JEGH and Tuohy pers. Obs.).…”
Section: Sponge Assemblagementioning
confidence: 99%